A importância do bruxismo, do estresse, depressão e ansiedade na sonolência diurna excessiva em estudantes universitários - Iglesias, Gabriela Ferreira [UNESP] (2015)
The excessive daytime sleepiness have undesirable consequences on health and social life of individuals. Bruxism is a frequent parafunctional habit in the young population, associated with emotional stress and is considered a sleep disorder that can lead to decreased quality of sleep and increased daytime sleepiness. In view of this, the aim of this study was to evaluate whether daytime sleepiness is related to the presence of bruxism, depression and emotional stress. For this, young students were selected through bruxism questionnaire, emotional stress and depression, and daytime sleepiness. The study included 128 young students volunteer dentistry, with 97 women and 31 men with no obstructive sleep apnea. They all responded to the Stress Symptom Inventory for Adults Lipp (ISSL) to identify stress symptoms, the Beck Depression Inventory for depressive symptoms. Also answered the Epworth Sleepiness index and a questionnaire about the presence of bruxism. The results were tabulated and analyzed statistically. After collecting the data, the group was divided into No (G1) and with (G2) excessive daytime sleepiness, and statistically analyzed using SPSS 20.0 (SPSS, Chicago, IL, USA) with alpha (α) = 0:05. The difference between the groups was analyzed using the chi-square test and Fisher for categorical variables and the Student t test for continuous variables. The Pearson test was used to verify the correlation between the variables. We can conclude that among the factors analyzed, only the females and depression correlate with excessive daytime sleepiness